Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Biro Layanan Pengadaan Dan Pengelolaan Barang Milik Negara Kementerian Perhubungan Di Wilayah III Yogyakarta, Solo Dan Surabaya - Agus Andri Setianto; Enas Enas (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Leadership in LPPBMN is currently being implemented in implementing units under the unit coordinator, so that the decision-making process requires more time. This leadership ineffectiveness has an impact on employees, including saturation in work effectiveness, which causes a decrease in the level of morale. Besides that, an uncomfortable work environment has an impact on decreased morale, resulting in low work performance. This study aims to determine 1) The influence of leadership on Employee morale, 2) The influence of the work environment on Employee morale, and 3) The influence of leadership and work environment on the morale of LPPBMN Kemenhub Employees. This research uses quantitative research methods. The results of the study show that leadership affects employee morale, the work environment influences employee morale, and leadership and work environment affect employee morale of LPPBMN Kemenhub. This means that the better the leadership and work environment, the morale will also increase, and vice versa.